(3ebOeI Gdi GdGfJQfJs - (3RjGO hCNQhf(B, (3GdbGVjs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2000)
(3jbOe gPG GdcJGH TQM eHSWddGfJQfjJ eY UhQ hQSheGJ dJSdjW GdeMJhi ceG jMcj HGdJOQL Yf JWhQ GdCfJQfjJs
Keywords: (3GfJQfJs; (3THcGJ GdEJUGds; (3hjHs